PHASE CONCENTRATION EQUILIBRIUM DURING DRYING COLLOID CAPILLARY-POROUS MATERIAL - PEA (ChemChemTech, 2024)
In this work, we studied experimentally the phase concentration equilibrium during drying of a colloidal capillary-porous material - peas. The studies were carried out by a static (exsicator) method using saturated aqueous solutions of mineral salts, with the help of which certain relative air humidity was created in the desiccators. To establish equilibrium, the samples were kept in desiccators for one month. The values of relative air humidity over salt solutions at the corresponding temperatures were found from the well-known Schneider diagram. Moisture desorption isotherms were determined, for which high-moisture pea samples were placed in exsicators. The experiments were carried out at three temperatures: 30, 40 and 50 °C. According to the measurement data, moisture desorption isotherms were constructed in the coordinates "relative air humidity - equilibrium moisture content of the material." The resulting desorption isotherms were described by the Henderson equation, for which the values of the coefficients of this equation were found and their statistical evaluation was given. The data on the balance of peas were compared with similar data for other plant colloidal capillary-porous materials: vegetables (carrot and beet cuts), grain crops (rye, wheat and corn grains), and vegetable seeds. A significant influence of the type of culture on the equilibrium moisture content of the material during drying is shown, while the intraspecific influence on the equilibrium moisture content is less important. The obtained data on moisture desorption isotherms during drying can be used for engineering calculations of the kinetics of drying pea grain and for choosing the temperature and humidity conditions for its storage after drying.